Determinan Pola Konsumsi Dharuriyyah, Hajiyyah dan Tahsiniyyah (Studi Kasus Pengguna Marketplace di Kota Malang) - Nanda Islachul Muslimah; Vietha Devia SS (Department of Islamic Economics, IPB University, 2023)
The advancement of technology in the era of digitalization offers convenience to consumers for quick and easy shopping through digital platforms such as marketplaces. Marketplaces provide various products and services, ranging from basic needs to luxury items. This convenience creates new opportunities and challenges in understanding consumer behavior, especially in terms of how a consumer's consumption patterns correspond with Islamic values in the context of meeting their needs. This research aims to analyze the determinants or factors influencing the consumption patterns of a Muslim consumer in meeting various levels of needs, such as financial literacy, hedonic motivation, technological proficiency, and price discounts. A case study was conducted on marketplace users in Malang City using a quantitative method and multiple linear regression analysis. The research results indicate that a consumer's financial literacy and technological proficiency, as well as the presence of price discounts, have an effect on their consumption patterns at the dharuriyyah, hajiyyah, and tahsiniyyah levels of need. However, hedonic motivation does not affect consumption patterns at all levels of needs. By understanding the effect of these factors on consumption patterns, this research offers valuable insights into how consumers perceive and prioritize their various needs in the ever-evolving digital environment.